Derivatives or climate insurance? Risk management tools for a soybean farmer in Brazil - Bortoluzzi Lorenzetti, Fernanda; Leismann, Edison Luiz; Rojo, Cláudio Antônio (Revista Competitividade e Sustentabilidade, 2021)
This paper aims to analyze whether there is a difference between the cost/benefit of climate risk reduction and cost/benefit of soybean price in Palotina, Paraná, Brazil. The data were collected from bibliography, official and private documents. Climate data were analyzed based on the releases content. The methodology to analyze de future market data was the same as the B3. Options were analyzed as Black & Scholes model. Also, this paper developed the Leismann & Bortoluzzi index to analyze the protections cost/benefit. To compare mitigation costs, there were used the t student test. Limitations were about the Black & Scholes model, which does not consider subjective variables. Cost/benefit index of price protections were compared with the climate insurance index in order to test if there was a statistical difference between them. All tests allowed to infer that the indices are statistically different. This study concluded that climate and price insurance are excellent tools for rural enterprise risk management, and there was significant evidence to infer that the protections are feasible. Or rather, that the farmer is exposed to both types of risk and that the forms of mitigation are satisfactory in both cases.